Students’ Perception on Using Blended Learning Method During Covid-19 Pandemic in Public Listening Subject - Dewi Chintia Kolbuniah; Abdul Ngafif; Basuki Basuki (Scripta : English Department Journal, 2022)
This research aims to know how the students’ perception of blended learning toward Public Listening subject during Covid-19 pandemic. The researchers collected the data through a questionnaires. There were 38 students from the 4th semester of English Language Education participated in this research. This research used descriptive qualitative research. From the data analisis, it is found that the students gave positive perceptions in following Public Listening subject by using Blended Learning method. From the computation, the highest average was 4.37 and the lowest average was 2.68. Moreover, there were 18 of 38 students felt excited during learning process. Furthermore, the students agreed with Blended Learning Method (combining online and offline) in Public Listening subject because it can improve their communication better than using offline or online method only with the procentage of satisfaction level 44.5% in which belongs to medium level. This study also found that the Blended Learning method benefited them and piqued their interest in learning. It also encourages student to be more active and responsible.